On the semi-scalar equivalence of polynomial matrices over a field (MCIT: Proceedings of International scientific and practical conference, 2021)
Polynomial matrices  and  of size  over a field  are semi-scalar equivalent if there exist a nonsingular  matrix  over  and an invertible  matrix  over  such that . The aim of the present report is to present a triangular form of some nonsingular polynomial matrices with respect to semi-scalar equivalence.
Keywords: Polynomial matrix, Equivalence of matrices, Smith normal form.